2020
DOI: 10.3390/biom11010018
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Approach to Explore the Interaction of Semisynthetic Nitrogenous Heterocyclic Compounds with the SARS-CoV-2 Main Protease

Abstract: In the context of the ongoing coronavirus disease 2019 (COVID-19) pandemic, numerous attempts have been made to discover new potential antiviral molecules against its causative agent, SARS-CoV-2, many of which focus on its main protease (Mpro). We hereby used two approaches based on molecular docking simulation to explore the interaction of four libraries of semisynthetic nitrogenous heterocyclic compounds with Mpro. Libraries L1 and L2 contain 52 synthetic derivatives of the natural compound 2-propylquinoline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Ghaleb et al also studied some pyridine N -oxide compounds, indicating the most potent one with a predicted pIC 50 (the negative log of the IC 50 when converted to molar) value of 5.294. More similar works can be found in the literature. …”
Section: Methods and Approachessupporting
confidence: 56%
“…Ghaleb et al also studied some pyridine N -oxide compounds, indicating the most potent one with a predicted pIC 50 (the negative log of the IC 50 when converted to molar) value of 5.294. More similar works can be found in the literature. …”
Section: Methods and Approachessupporting
confidence: 56%
“…Recently, studies have illustrated that N-heterocyclic compounds possess antiviral activity. Thus, they can be used as potential noncovalent inhibitors of 3CL pro of SARS-CoV-2. Some of the most prominent nitrogen-containing heterocycles are the purine scaffolds, which have attracted medicinal interest due to their applications as drug candidates in cancer treatment and viral disorders. , Also, there is a considerable tendency to study new heterocyclic fused imidazopyridine derivatives containing abundant biological activities, such as anticancer, , antiprotozoal agent, antiviral, anti-inflammatory, and anti-Alzheimer’s disease activities. Recent investigations have revealed that the heterocyclic systems with additional fused rings display more effective pharmacological and physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Reserpine was documented to have a robust antiviral activity against severe acute respiratory syndrome coronavirus (SARS-CoV) with an EC 50 value of 3.4 µM 15 whilst in our findings, it proved moderate anti-influenza potential against the human influenza A/H1N1 virus. Similarly, an in silico study for the antiviral activity of the Eserine (or Physostigmine) derivatives against pandemic SARS-CoV-2 proved their ability to combat the coronavirus action 14 . However, the purified compound of the Eserine used in this study showed no antiviral activity against the human influenza A/H1N1 virus.…”
Section: Discussionmentioning
confidence: 97%
“…Indole alkaloids class are those alkaloids with an organic structure consisting of a pyrrole linked to a benzene ring. Such compounds are produced from plants as secondary metabolites, and they exhibited antiviral activities against a wide variety of viruses such as IAV 9 , hepatitis C virus (HCV) 10 , human immunodeficiency virus-1 (HIV-1) 11 , dengue virus (DENV) 12 , zika virus (ZIKV) and chikungunya virus (CHIKV) 13 and may play a key role in combating the newly emerged coronavirus; severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) 14 16 . The aromatic compounds: β-carbolines (naturally and/or synthetically indole alkaloid derivatives) possess numerous biological activities including antiviral activities against different emerging and reemerging viruses such as herpes simplex virus-1 (HSV-2), DENV-2, and enterovirus-71 (EV-71), HIV and Poliovirus (PV) 17 20 .…”
Section: Introductionmentioning
confidence: 99%